Jenis Udang Air Tawar di Salah Satu Sungai di Indonesia - Purnamasari, Lora (Universitas PGRI Sumatera Barat, 2017)
The purpose of this research is to study the species of freshwater shrimp in one of the rivers in Indonesia.Sampling was conducted in the Manna River Basin consisting of Ketaman River and Langkap River. Determination of shrimp sampling location was done purposively, Â followed by road sampling method upstream for 1 hour as far as 10 m. The results obtained from freshwater shrimp from families Palamonidae, genera Macrobrachium consisted of species Macrobrachium lanchesteri and Macrobrachium sintangense. M. lanchesteri most commonly found with the number of thirtynine individuals, while species Macrobrchium sintangense amounted to nineteen individuals.